The Role of Social Media in Online Marketing for MSMEs - Kuswanto, Nawang Maulida (Economic and Business Horizon, 2024)
The development of information technology has transformed societal behavior patterns, particularly in the field of business marketing. This study aims to analyze the differences and similarities between online marketing and social media, as well as to explore the strategic role of social media in supporting marketing activities, especially for Micro, Small, and Medium Enterprises (MSMEs). This research employs a descriptive qualitative approach through a literature review of relevant sources. The findings show that although online marketing and social media share a common goal—attracting market attention and understanding consumer behavior through data analysis—they differ in scope and focus. Online marketing encompasses various digital strategies such as email marketing, SEO, and paid advertising, while social media focuses on direct interaction with consumers through platforms like Instagram, Facebook, and TikTok. For MSMEs, social media offers several key functions, including customer identification, two-way communication, product information dissemination, monitoring consumer preferences, and building customer loyalty. Proper utilization of social media can serve as a strategic tool to expand market reach and enhance MSME competitiveness in the digital era.